Intravitreal Avastin for macular oedema secondary to retinal vein occlusion: a prospective study. Issue 4 (22nd January 2008) - Kriechbaum, K; Michels, S; Prager, F; Georgopoulos, M; Funk, M; Geitzenauer, W; Schmidt-Erfurth, U
Abstract : Objective: To evaluate efficacy and safety of intravitreal bevacizumab (Avastin) in eyes with macular oedema secondary to central retinal vein occlusion (CRVO) or branch retinal vein occlusion (BRVO). Methods: Twenty-eight consecutive patients (28 patients, 29 eyes, 8 CRVO, 21 BRVO) were enrolled in the study. Three intravitreal injections of 1 mg bevacizumab (0.04 ml) were administered at 4-week intervals; further retreatment was based on optical coherence tomography (OCT) findings. Follow-up examinations were done at days 1, 7 and 28 and at monthly intervals thereafter. Results: Mean baseline central retinal thickness (CRT) in OCT was 558 µm (range 353–928 µm) and mean BCVA was 20/100. One day after the first injection, CRT significantly decreased to 401 μm (p<0.01). Three injections reduced macular oedema to 328 μm CRT (p<0.01) and improved BCVA to 20/50 (p<0.01). At 6 months, CRT was 382 μm (p<0.01), and BCVA was stable at 20/50 −2 (p<0.01), FA showed no evidence of increased avascular zones. Conclusion: Intravitreal injections of bevacizumab appear to be a safe and effective therapy in the treatment of macular oedema secondary to retinal vein occlusion.